Performativity and intersemiotic translation in contemporary art: the case of Hong Kong Atlas. - Poposki, Zoran; Todorova, Marija (Visual Studies, 2024)
This paper considers the intersection of performativity and intersemiotic translation in contemporary art through a case study of a new media art project aimed at visually transcoding Dung Kai-Cheung's novel Atlas: The Archaeology of an Imaginary City, a book of postmodern fiction about the palimpsest nature of Hong Kong as a linguistic landscape and a city of (cultural) translation. In Hong Kong Atlas, the locations in Dung's book are performatively mapped out onto the real semioscape of contemporary Hong Kong using psychogeography documented in digital images, which are then transcoded through a series of iterative translations into a variety of visual formats. By analysing the complex methodology and the unique interdisciplinary theoretical framework underpinning this artistic research (combining insights from fields such as visual studies, translation studies, sociolinguistics, multimodal discourse analysis, art theory, and practice-based research epistemology), the article aims to provide a novel approach to the discussion of visual translation as intersemiotic translation.